Analisis Tingkat Kesejahteraan Rumahtangga Petani Jambu Mete di Kabupaten Buton Utara - Fyka, Samsul Alam; Yusria, Wa Ode; Limi, Muhammad Aswar; Safitria, Safitria (Department of Agribusiness Halu Oleo University Kendari Southeast Sulawesi, 2019)
The purpose of this study was to determine the level of welfare of cashew farmer households due to the development of cashew farming through the role of the local government. The research was conducted in 2018 in the North Kulisusu District by selecting three villages, namely Bira Village, Kurolabu Village, and Lakansai Village. The location selection was done purposively because this area was one of the regions that experienced an increase in the development of cashew cultivation. Determination of respondents is done by quota sampling, which is 20 people per village, so the number of respondents is 60 people. Data collection uses techniques (1) interviews, (2) observations, and (3) questionnaires. Data collection is done by direct communication with farmers, and parties related to cashew farming. The measurement of the level of welfare is carried out by analyzing the Farmer's Household Exchange Rate. The results of this study are the structure of cashew farmer household income, which is 40.18% or Rp62,227,167, - from the agricultural sector while 59.82% or Rp92,650,000, - from the non-agricultural sector. So that the level of household welfare of cashew farmers is prosperous with NTPRP values > 1 which is 7,8